Examination of Secondary School Students' Attitudes towards Communication and Collaboration Skills in Terms of Some Variables - Kocaman , Berrak (Asian Journal of Education and Training, 2022)
This study aims to examine the communication and collaboration attitudes of secondary school students according to some variables and to determine if there is a relationship between students' communication and collaboration attitudes. The survey model was used in the study, and the sample consists of 405 secondary school students studying in Salihli, Manisa. “Secondary school students’ communication attitude scale (SSSCAS)” and “Scale for Self-Evaluation of Collaboration Skills (SSCS)” were used to collect data. According to analysis results of the data obtained, it was found out that the communication and collaboration attitudes of the secondary school students were at a high level and did not show statistically significant differences in terms of gender and educational status of the parents. On the other hand, there was a significant difference according to owning tablet/PC variable. Besides, there is a positive relationship between secondary school students' communication skills attitude and collaboration attitudes.